MapSwipe: global dataset of crowdsourced classifications on human settlements and reference datasets - Herfort, Benjamin (Universität, 2018)
MapSwipe is a mobile crowdsourcing application designed for smartphones and tablets to generate geographic information from satellite imagery. Data from 55 projects containing more than nine million tasks and more than 30 million individual classification results contributed by about 7,500 users are covered by this dataset. Furthermore, reference datasets obtained manually and derived from OpenStreetMap are provided.
Gesehen am 19.04.2018
Time period covered: Start: 2016-07-30 ; end: 2017-07-25
Kind of data: Crowdsourced classifications
Keywords: Forschungsdaten; Datenbank